Scaffold-free parathyroid tissue engineering using tonsil-derived mesenchymal stem cells. (15th April 2016) - Park, Yoon Shin; Hwang, Ji-Young; Jun, Yesl; Jin, Yoon Mi; Kim, Gyungah; Kim, Ha Yeong; Kim, Han Su; Lee, Sang-Hoon; Jo, Inho
Graphical abstract: Abstract: To restore damaged parathyroid function, parathyroid tissue engineering is the best option. Previously, we reported that differentiated tonsil-derived mesenchymal stem cells (dTMSC) restore in vivo parathyroid function, but only if they are embedded in a scaffold. Because of the limited biocompatibility of Matrigel, however, here we developed a more clinically applicable, scaffold-free parathyroid regeneration system. Scaffold-free dTMSC spheroids were engineered in concave microwell plates made of polydimethylsiloxane in control culture medium for the first 7 days and differentiation medium (containing activin A and sonic hedgehog) for next 7 days. The size of dTMSC spheroids showed a gradual and significant decrease up to day 5, whereafter it decreased much less. Cells in dTMSC spheroids were highly viable (>80%). They expressed high levels of intact parathyroid hormone (iPTH), the parathyroid secretory protein 1, and cell adhesion molecule, N-cadherin. Furthermore, dTMSC spheroids-implanted parathyroidectomized (PTX) rats revealed higher survival rates (50%) over a 3-month period with physiological levels of both serum iPTH (57.7–128.2 pg/mL) and ionized calcium (0.70–1.15 mmol/L), compared with PTX rats treated with either vehicle or undifferentiated TMSC spheroids. This is the first report of a scaffold-free, human stem cell-based parathyroid tissue engineering and represents a more clinically feasible strategy for hypoparathyroidism treatment than those requiring scaffolds. Statement of Significance: Herein, we have for the first time developed a scaffold-free parathyroid tissue spheroids using differentiated tonsil-derived mesenchymal stem cells (dTMSC) to restore in vivo parathyroid cell functions. This new strategy is effective, even for long periods (3 months), and is thus likely to be more feasible in clinic for hypoparathyroidism treatment. Development of TMSC spheroids may also provide a convenient and efficient scaffold-free platform for researchers investigating conditions involving abnormal calcium homeostasis, such as osteoporosis.